The Role of Sports Practice in Young Adolescent Development of Moral Competence - Małgorzata Bronikowska (International Journal of Environmental Research and Public Health, 2020)
The study examined the moral competence levels in adolescents participating in individual/team sports compared with those not undertaking sports at all. In total, 827 students aged 15–17 years old (45.4% boys, 54.6% girls) from randomly selected secondary schools in the Wielkopolska region in Poland participated in the study. The moral competences were assessed using the Lind’s Moral Competence Test. The students also answered questions concerning their statues of involvement in sport (not involved; amateur; professional), years of involvement, and the type of sport they partook in (individual/team). The results highlight that the moral competence level in most of the examined adolescents (71.6% girls, 76.8% boys) was low. Those who presented a high moral competence level were 10.4% in girls, 8% in boys. There was no interaction between modes of involvement in sport and moral competence when comparing adolescents. The moral competence levels were not correlated with years of training in either mode of involvement or with type of sports. Therefore, we assume that, at this age, the type of sport and the level of engagement do not differentiate moral competence level and that there must be more factors contributing to this. This opens new directions for further research on the role of external factors stimulating the socio-moral growth of youth.